A bad turn deserves another: Linkages between terrorism, capital flight and industrialisation - Simplice Asongu; Joseph Nnanna; Rexon T. Nting (African Governance and Development Institute (AGDI), 2021)
This study examines how the association between terrorism and capital flight affects the process of industrialisationin 36 African countries. The empirical evidence is based on Generalised Method of Moments (GMM) and Quantile Regressions (QR). GMM-oriented findings show that capital flight interacts with terrorism to negatively affect industrialisation in 'domestic terrorism'- and 'total terrorism'-oriented regressions. With QR approach, the GMM results are confirmed exclusively in the 25th and 50th quantiles, in regressions pertaining to domestic terrorism, unclear terrorism and total terrorism. It follows that the negative effect from the investigated interaction is driven by bottom quantiles of the industrialisation distribution. This confirms existing literature that developed countries are more likely to limit the negative externalities from terrorism compared to their developing counterparts. Hence, the negative consequence of the association between terrorism and capital flight on industrialisation is a decreasing function of industrialisation.
Keywords: C50; D74; F23; N40; O55; 330; Capital flight; terrorism; industrialisation; Africa